(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
this article describes the theoretical foundations and relevance of the concept of food supply. In addition, the theoretical basis and conditions of food safety are also explained. The opinions of economists who have conducted research on this topic in order to better illuminate the theoretical foundations of food supply and safety are also cited.